High-entropy conversion-alloy-based negative electrode material in potassium / sodium ion battery and preparation method of high-entropy conversion-alloy-based negative electrode material

Through the medium-high entropy conversion-alloy dual reaction mechanism negative electrode material SbxBiySnzComMnnNi2-x-y-z-m-nTe3, the problem of volume expansion and electrochemical kinetic behavior of the anode material of potassium/sodium ion battery during sodium storage is solved, and excellent rate performance and long-term Cycling life, suitable for commercial production.

CN119252910AActive Publication Date: 2025-01-03NORTHWESTERN POLYTECHNICAL UNIV +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411123188.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-15
Publication Date
2025-01-03
Estimated Expiration
2044-08-15

AI Technical Summary

Technical Problem

Potassium/sodium ion battery negative electrode materials have large volume expansion and slow electrochemical kinetic behavior during potassium/sodium storage, which limits its rate performance and cyclic stability.

Method used

The negative electrode material SbxBiySnzComMnnNi2-x-y-z-m-nTe3 was used to prepare the material by hydrothermal method, and the high entropy and multivariate synergistic effect was used to suppress volume expansion, enhancing the kinetic behavior of electron transport and ion diffusion.

Benefits of technology

It effectively suppresses volume expansion during charging and discharging, enhances rate performance and cycle life, combines high reversible specific capacity and structural stability, and has simple preparation technology and low cost, making it suitable for large-scale commercial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119252910A_ABST
    Figure CN119252910A_ABST
Patent Text Reader

Abstract

The invention discloses a high-entropy conversion-alloy-based negative electrode material in a potassium / sodium ion battery and a preparation method of the high-entropy conversion-alloy-based negative electrode material. The preparation method of the material comprises the following steps: weighing a certain amount of antimony salt, bismuth salt, tin salt, cobalt salt, manganese salt and nickel salt according to a stoichiometric ratio, and dissolving in deionized water containing tartaric acid to form a uniform solution A; secondly, dissolving a certain amount of sodium tellurite in ammonia water containing hydrazine hydrate to form a uniform solution B; uniformly mixing the solution A and the solution B, and carrying out hydrothermal reaction; and centrifuging, washing and drying to obtain a target'medium-high entropy 'material. The potassium / sodium storage electrochemical kinetics behavior of the conversion-alloy-based negative electrode material can be remarkably enhanced through the middle-high entropy component design, and the problem of large volume expansion in the charging and discharging process is effectively inhibited, so that the material has high reversible specific capacity and excellent cycling stability and rate capability; in addition, the preparation process is simple, easy to operate and suitable for large-scale industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of negative electrode materials for potassium and sodium ion batteries, and in particular relates to a "medium-high entropy" conversion-alloy dual reaction mechanism negative electrode material and a preparation method thereof. Background Art

[0002] Lithium-ion batteries are widely used in portable electronic devices and electric vehicles due to their high energy density, high power density and long cycle life. However, due to the shortage and uneven distribution of lithium ore raw materials, lithium-ion batteries cannot meet the needs of the rapidly growing electric vehicle market and future large-scale energy storage devices. Given that sodium-ion batteries and potassium-ion batteries have the advantages of abundant raw material reserves and low cost compared to lithium-ion batteries, and that the three have similar "rocking chair" electrochemical working principles, sodium / potassium-ion batteries are low-cost energy storage devices with great research prospects.

[0003] At present, the negative electrode of potassium / sodium ion batteries can be divided into three types of materials: insertion type, conversion type and alloy reaction mechanism. Insertion type mechanism materials have lower working voltage and excellent cycle stability, but due to their limited actual specific capacity, they greatly limit the upper limit of the energy density of potassium / sodium ion batteries. In contrast, conversion or alloy reaction mechanism materials can provide high theoretical specific capacity through multi-electron transfer reactions, but they have large volume expansion and slow electron and ion transfer kinetics during potassium / sodium storage, thus deteriorating cycle stability and rate performance. In recent years, new negative electrode materials based on conversion-alloy dual reaction mechanism can contribute higher theoretical specific capacity due to the conversion reaction of cations and the alloying reaction of metal elements. Secondly, the participation of alloy reaction can reduce the working voltage of the material, and the conversion product can also serve as a buffer area to accommodate the large lattice stress generated during the alloying / de-alloying process. The introduction of medium and high entropy components can further enhance the electrochemical kinetic behavior by reducing the band gap width of the material and the diffusion barrier of potassium / sodium ions. At the same time, the increase in disorder can effectively enhance the electrode morphology and structural stability in the electrochemical process, thereby improving the rate performance and cycle stability. Summary of the invention

[0004] The purpose of the present invention is to improve the large volume expansion problem and sluggish electrochemical kinetic behavior of conversion or alloy reaction mechanism negative electrode materials during potassium / sodium storage, and propose a "medium-high entropy" conversion-alloy dual reaction mechanism negative electrode material and its preparation method.

[0005] A high entropy conversion-alloy-based negative electrode material in a potassium / sodium ion battery, characterized in that the chemical formula of the negative electrode material is Sb x Bi y Sn z Co m Mn nNi 2-x-y-z-m-n Te3, wherein 0≤x<2, 0≤y<2, 0≤z<2, 0≤m<2, 0≤n<2, and at least three elements among Sb, Bi, Sn, Co, Mn, and Ni are present.

[0006] A method for preparing a high entropy conversion-alloy-based negative electrode material in a potassium / sodium ion battery, characterized in that it comprises the following steps:

[0007] (1) weighing a certain amount of antimony salt, bismuth salt, tin salt, cobalt salt, manganese salt and nickel salt according to a stoichiometric ratio and dissolving them in deionized water containing tartaric acid to form a uniform solution A; secondly dissolving a certain amount of sodium tellurite in ammonia water containing hydrazine hydrate to form a uniform solution B;

[0008] (2) mixing solution A and solution B evenly under stirring conditions, transferring the mixture to a reaction vessel lined with polytetrafluoroethylene, and performing a hydrothermal reaction under certain temperature and time conditions;

[0009] (3) obtaining a precipitate by centrifugation or filtration, washing the precipitate with deionized water and ethanol, and finally obtaining the target product Sb by vacuum drying. x Bi y Sn z Co m Mn n Ni 2-x-y-z-m-n Te3.

[0010] A further technical solution of the present invention: the antimony salt, bismuth salt, tin salt, cobalt salt, manganese salt and nickel salt described in step (1) can be one or more of chloride, sulfate and nitrate.

[0011] A further technical solution of the present invention is as follows: the molar ratio of the sodium tellurite and the total amount of the metal salt in step (1) is 2.5 to 3.1:2.

[0012] A further technical solution of the present invention is as follows: in step (2), the stirring temperature is 20 to 60° C. and the stirring time is 0.5 to 4 h.

[0013] A further technical solution of the present invention: the hydrothermal reaction temperature in step (2) is 120-220° C., and the hydrothermal reaction insulation time is 2-12 h.

[0014] A further technical solution of the present invention: the vacuum drying temperature in step (3) is 50 to 100° C., and the vacuum drying time is 6 to 36 hours.

[0015] Compared with the prior art, the present invention has the following advantages:

[0016] (1) The "medium-high entropy" negative electrode material for potassium / sodium ion batteries prepared by the present invention can effectively inhibit the large volume expansion generated during the charge and discharge process and enhance the electron transport and ion diffusion kinetics through high entropy and multi-element synergistic effects, thereby ensuring that the material exhibits excellent rate performance and long cycle life.

[0017] (2) The negative electrode material prepared by the present invention combines the advantages of both conversion and alloy reactions. On the one hand, it ensures a high reversible specific capacity based on the multi-electron transfer reaction, and on the other hand, it enhances the kinetic process and structural stability through the coupling effect of the dual mechanism.

[0018] (3) The preparation process of the present invention is simple, the equipment operation is simple and the cost is low, the product preparation success rate is high, and it is green and environmentally friendly, and is suitable for large-scale commercial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 The Sb prepared in Example 1 of the present invention 1.4 Bi 0.2 Sn 0.2 Co 0.1 Mn 0.1 X-ray diffraction (XRD) pattern of Te3 negative electrode material;

[0020] Figure 2 The Sb prepared in Example 1 of the present invention 1.4 Bi 0.2 Sn 0.2 Co 0.1 Mn 0.1 Transmission electron microscope (TEM) image of Te3 negative electrode material;

[0021] Figure 3 The Sb prepared in Example 1 of the present invention 1.4 Bi 0.2 Sn 0.2 Co 0.1 Mn 0.1 Cyclic voltammetry curve of Te3 negative electrode material in potassium ion battery;

[0022] Figure 4 The Sb prepared in Example 1 of the present invention 1.4 Bi 0.2 Sn 0.2 Co 0.1 Mn 0.1 The charge and discharge curves of Te3 negative electrode materials in potassium ion batteries;

[0023] Figure 5 The Sb prepared in Example 1 of the present invention 1.4 Bi 0.2 Sn 0.2 Co0.1 Mn 0.1 Cycling performance diagram of Te3 negative electrode material in potassium ion battery at 20mA / g current density;

[0024] Figure 6 The Sb prepared in Example 1 of the present invention 1.4 Bi 0.2 Sn 0.2 Co 0.1 Mn 0.1 Rate performance diagram of Te3 negative electrode material in potassium ion battery.

[0025] Figure 7 The Sb prepared in Example 2 of the present invention 0.7 Bi 0.7 Sn 0.6 X-ray diffraction (XRD) pattern of Te3 negative electrode material;

[0026] Figure 8 The Sb prepared in Example 2 of the present invention 0.7 Bi 0.7 Sn 0.6 Scanning electron microscope (SEM) image of Te3 negative electrode material;

[0027] Fig. 9 The Sb prepared in Example 2 of the present invention 0.7 Bi 0.7 Sn 0.6 Cyclic voltammetry curve of Te3 negative electrode material in potassium ion battery;

[0028] Fig.10 The Sb prepared in Example 2 of the present invention 0.7 Bi 0.7 Sn 0.6 The charge and discharge curves of Te3 negative electrode materials in potassium ion batteries;

[0029] Fig.11 The Sb prepared in Example 2 of the present invention 0.7 Bi 0.7 Sn 0.6 Cycling performance diagram of Te3 negative electrode material in potassium ion battery at 50mA / g current density;

[0030] Fig.12 The Sb prepared in Example 3 of the present invention 0.4 Bi 0.4 Sn 0.3 Co 0.3 Ni 0.3 Mn 0.3 X-ray diffraction (XRD) pattern of Te3 negative electrode material;

[0031] Fig.13 The Sb prepared in Example 3 of the present invention 0.4 Bi 0.4 Sn 0.3 Co 0.3 Ni 0.3 Mn 0.3 Scanning electron microscope (SEM) image of Te3 negative electrode material;

[0032] Fig.14 The Sb prepared in Example 3 of the present invention 0.4 Bi 0.4 Sn 0.3 Co 0.3 Ni 0.3 Mn 0.3 Cyclic voltammetry curve of Te3 negative electrode material in potassium ion battery;

[0033] Fig.15 The Sb prepared in Example 3 of the present invention 0.4 Bi 0.4 Sn 0.3 Co 0.3 Ni 0.3 Mn 0.3 The charge and discharge curves of Te3 negative electrode materials in potassium ion batteries;

[0034] Fig.16 The Sb prepared in Example 3 of the present invention 0.4 Bi 0.4 Sn 0.3 Co 0.3 Ni 0.3 Mn 0.3 Cycling performance diagram of Te3 negative electrode material in potassium ion battery at 20mA / g current density;

[0035] Fig.17 The Sb prepared in Example 3 of the present invention 0.4 Bi 0.4 Sn 0.3 Co 0.3 Ni 0.3 Mn 0.3 Rate performance diagram of Te3 negative electrode material in potassium ion battery. DETAILED DESCRIPTION

[0036] The present invention will be further described below with reference to specific embodiments, but the present invention is not limited thereto.

[0037] Example 1

[0038] (1) 0.7 mmol antimony trichloride, 0.1 mmol bismuth trichloride, 0.1 mmol stannous chloride, 0.05 mmol cobalt chloride, and 0.05 mmol manganese chloride were dissolved in 10 ml deionized water containing 1.0 g tartaric acid to form a uniform solution A; secondly, 1.4 mmol sodium tellurite was dissolved in 40 ml ammonia water containing 16 ml hydrazine hydrate to form a uniform solution B;

[0039] (2) Solution A and Solution B were stirred at 20° C. for 1.5 h, transferred to a reaction vessel lined with polytetrafluoroethylene, and kept at 170° C. for 6 h for hydrothermal reaction;

[0040] (3) After cooling to room temperature, the precipitate was obtained by centrifugation, and the precipitate was washed with deionized water and ethanol, and finally vacuum dried at 60°C for 12 h to obtain the target product Sb 1.4 Bi 0.2 Sn 0.2 Co 0.1 Mn 0.1 Te3.

[0041] The Sb prepared in this example was mixed with water in a mass ratio of 8:1:1. 1.4 Bi 0.2 Sn 0.2 Co 0.1 Mn 0.1 Te3, acetylene black and polyvinylidene fluoride were dissolved in N-methylpyrrolidone, stirred into a uniform slurry and coated on the copper foil current collector. After drying at 80°C for 15 hours, they were cut into sheets with a diameter of 12 mm. Potassium / sodium metal was used as the negative electrode, glass fiber membrane was used as the separator, and 1M KFSI or NaClO4 solution (the solvent was EC and DEC in a volume ratio of 1:1) was used as the electrolyte. The half-cell was assembled in an argon-filled glove box, and constant current charge and discharge tests were performed in the voltage range of 0.01 to 3.0 V.

[0042] Figure 1 The Sb prepared in this example is given 1.4 Bi 0.2 Sn 0.2 Co 0.1 Mn 0.1 The Rietveld refined X-ray diffraction (XRD) pattern of the Te3 negative electrode material shows that its crystal structure corresponds to the hexagonal system with R-3m space group (PDF#97-018-4226).

[0043] Figure 2 Given Sb 1.4 Bi 0.2 Sn 0.2 Co 0.1 Mn 0.1Transmission electron microscope (TEM) image of Te3 negative electrode material, Sb 1.4 Bi 0.2 Sn 0.2 Co 0.1 Mn 0.1 Te3 is a hexagonal nanosheet with a size of about 300 nm.

[0044] Figure 3 Given by Sb 1.4 Bi 0.2 Sn 0.2 Co 0.1 Mn 0.1 Cyclic voltammetry curve of Te3 during potassium ion storage, the reduction peak at 1.38V and the oxidation peak at 1.99V correspond to Sb 1.4 Bi 0.2 Sn 0.2 Co 0.1 Mn 0.1 Insertion and extraction reactions of Te3; the reduction peak at 0.95V and the oxidation peak at 1.64V correspond to the conversion and reverse conversion processes of the material; the reduction peak at 0.15V and the oxidation peak at 0.83V are the alloying and reverse alloying reactions that occur during the potassium storage process.

[0045] Figure 4 Given Sb 1.4 Bi 0.2 Sn 0.2 Co 0.1 Mn 0.1 The charge and discharge curve of Te3 negative electrode material during potassium storage shows obvious conversion and alloy charge and discharge platform. The first reversible specific capacity of the material is 372.9 mAh / g.

[0046] Figure 5 Given Sb 1.4 Bi 0.2 Sn 0.2 Co 0.1 Mn 0.1 The cycle performance diagram of Te3 negative electrode material at a current density of 20mA / g shows that the charging capacity after 150 cycles is as high as 207.4mAh / g, and the charge and discharge efficiency is as high as 100%.

[0047] Figure 6 Given Sb 1.4 Bi 0.2 Sn 0.2 Co 0.1 Mn 0.1The rate performance diagram of Te3 negative electrode material in the potassium storage process shows that the reversible specific capacity at current densities of 50, 100, 200, 500, 1000, and 2000 mA / g is 387.5, 326.8, 290.3, 236.9, 178.4, and 93.9 mAh / g, respectively. When the current is restored to 50 mA / g, the reversible specific capacity can be restored to 359.1 mAh / g.

[0048] It can be seen that a pure phase Sb-Bi-Sn-Co-Mn based high entropy telluride can be constructed by a one-step hydrothermal method. Based on high entropy stability and five-element synergistic effect, the electron and ion transport kinetics and potassium storage structure stability can be effectively enhanced, thus significantly improving the electrochemical performance of the conversion-alloy negative electrode material.

[0049] Example 2

[0050] (1) 0.35 mmol antimony trichloride, 0.35 mmol bismuth nitrate, and 0.3 mmol stannous chloride were dissolved in 10 ml deionized water containing 1.0 g tartaric acid to form a uniform solution A; secondly, 1.5 mmol sodium tellurite was dissolved in 40 ml ammonia water containing 16 ml hydrazine hydrate to form a uniform solution B;

[0051] (2) Solution A and Solution B were stirred at 40°C for 1 h, transferred to a reaction vessel lined with polytetrafluoroethylene, and kept at 180°C for 4 h for hydrothermal reaction;

[0052] (3) After cooling to room temperature, the precipitate was obtained by centrifugation, and the precipitate was washed with deionized water and ethanol, and finally vacuum dried at 80°C for 8 h to obtain the target product Sb 0.7 Bi 0.7 Sn 0.6 Te3.

[0053] The Sb prepared in this example was mixed with water in a mass ratio of 8:1:1. 0.7 Bi 0.7 Sn 0.6 Te3, acetylene black and polyvinylidene fluoride were dissolved in N-methylpyrrolidone, stirred into a uniform slurry and coated on the copper foil current collector. After drying at 80°C for 15 hours, they were cut into sheets with a diameter of 12 mm. Potassium / sodium metal was used as the negative electrode, glass fiber membrane was used as the separator, and 1M KFSI or NaClO4 solution (the solvent was EC and DEC in a volume ratio of 1:1) was used as the electrolyte. The half-cell was assembled in an argon-filled glove box, and constant current charge and discharge tests were performed in the voltage range of 0.01 to 3.0 V.

[0054] Figure 7 The Sb prepared in this example is given 0.7 Bi 0.7 Sn0.6 The Rietveld refined X-ray diffraction (XRD) pattern of the Te3 negative electrode material shows that the crystal structure belongs to the hexagonal system of the R-3m space group (PDF#97-018-4226).

[0055] Figure 8 Given Sb 0.7 Bi 0.7 Sn 0.6 Scanning electron microscope (SEM) image of Te3 negative electrode material, Sb 0.7 Bi 0.7 Sn 0.6 Te3 is a hexagonal nanosheet with a size of about several micrometers.

[0056] Fig. 9 The Sb 0.7 Bi 0.7 Sn 0.6 Cyclic voltammetry curve of Te3, the reduction peak at 1.40V and the oxidation peak at 2.05V are attributed to Sb 0.7 Bi 0.7 Sn 0.6 Insertion and extraction reactions of Te3; the reduction peak at 1.01V and the oxidation peak at 1.65V correspond to the conversion and reverse conversion processes of the material; the reduction peak at 0.15V and the oxidation peak at 0.57V are the alloying and reverse alloying reactions that occur during the potassium storage process.

[0057] Fig.10 Given Sb 0.7 Bi 0.7 Sn 0.6 The charge and discharge curve of Te3 negative electrode material during potassium storage shows obvious conversion and alloy charge and discharge platform. The first reversible specific capacity of the material is 364.1 mAh / g.

[0058] Fig.11 Given Sb 0.7 Bi 0.7 Sn 0.6 The cycle performance diagram of Te3 negative electrode material at a current density of 50mA / g shows that the charging capacity after 50 cycles is as high as 266.0mAh / g, and the charge and discharge efficiency is as high as 96.1%.

[0059] It can be seen that the pure phase Sb was successfully prepared by hydrothermal method. 0.7 Bi 0.7 Sn 0.6 Te3 intermediate entropy negative electrode material. This negative electrode material effectively suppresses the large volume expansion of the material during the charge and discharge process through intermediate entropy and ternary synergistic effects, and improves the electrochemical kinetic behavior of the material, thus showing excellent electrochemical performance.

[0060] Example 3

[0061] (1) 0.2 mmol antimony nitrate, 0.2 mmol bismuth nitrate, 0.15 mmol stannous chloride, 0.15 mmol cobalt nitrate, 0.15 mmol nickel nitrate, and 0.15 mmol manganese nitrate were dissolved in 10 ml deionized water containing 1.0 g tartaric acid to form a uniform solution A; secondly, 1.45 mmol sodium tellurite was dissolved in 40 ml ammonia water containing 16 ml hydrazine hydrate to form a uniform solution B;

[0062] (2) stirring solution A and solution B at 60° C. for 0.5 h, transferring them to a reactor lined with polytetrafluoroethylene, and keeping them at 200° C. for 2 h for hydrothermal reaction;

[0063] (3) After cooling to room temperature, the precipitate was obtained by centrifugation, and the precipitate was washed with deionized water and ethanol, and finally vacuum dried at 90°C for 6 h to obtain the target product Sb 0.4 Bi 0.4 Sn 0.3 Co 0.3 Ni 0.3 Mn 0.3 Te3.

[0064] The Sb prepared in this example was mixed with water in a mass ratio of 8:1:1. 0.4 Bi 0.4 Sn 0.3 Co 0.3 Ni 0.3 Mn 0.3 Te3, acetylene black and polyvinylidene fluoride were dissolved in N-methylpyrrolidone, stirred into a uniform slurry and coated on the copper foil current collector. After drying at 80°C for 15 hours, they were cut into sheets with a diameter of 12 mm. Potassium / sodium metal was used as the negative electrode, glass fiber membrane was used as the separator, and 1M KFSI or NaClO4 solution (the solvent was EC and DEC in a volume ratio of 1:1) was used as the electrolyte. The half-cell was assembled in an argon-filled glove box, and constant current charge and discharge tests were performed in the voltage range of 0.01 to 3.0 V.

[0065] Fig.12 The Sb prepared in this example is given 0.4 Bi 0.4 Sn 0.3 Co 0.3 Ni 0.3 Mn 0.3 The Rietveld refined X-ray diffraction (XRD) pattern of the Te3 negative electrode material shows that its crystal structure corresponds to the hexagonal system with R-3m space group (PDF#97-018-4226).

[0066] Fig.13 Given Sb 0.4 Bi 0.4 Sn 0.3 Co 0.3 Ni 0.3 Mn 0.3 Scanning electron microscope (SEM) image of Te3 negative electrode material, Sb 0.4 Bi 0.4 Sn 0.3 Co 0.3 Ni 0.3 Mn 0.3 Te3 is a hexagonal nanosheet with a size of about several micrometers.

[0067] Fig.14 Given by Sb 0.4 Bi 0.4 Sn 0.3 Co 0.3 Ni 0.3 Mn 0.3 Cyclic voltammetry curve of Te3 during potassium ion storage, the reduction peak at 1.42V and the oxidation peak at 2.09V correspond to Sb 0.4 Bi 0.4 Sn 0.3 Co 0.3 Ni 0.3 Mn 0.3 Insertion and extraction reactions of Te3; the reduction peak at 0.26V and the oxidation peak at 1.75V correspond to the conversion and reverse conversion processes of the material; the reduction peak at 0.08V and the oxidation peak at 0.89V are the alloy and reverse alloy reactions that occur during the potassium storage process.

[0068] Fig.15 Given Sb 0.4 Bi 0.4 Sn 0.3 Co 0.3 Ni 0.3 Mn 0.3 The charge and discharge curve of Te3 negative electrode material during potassium storage shows obvious conversion and alloy charge and discharge platform. The first reversible specific capacity of the material is 397.2mAh / g.

[0069] Fig.16 Given Sb 0.4 Bi 0.4 Sn 0.3 Co 0.3 Ni 0.3 Mn 0.3 The cycle performance diagram of Te3 negative electrode material at a current density of 50mA / g shows that the charging capacity after 100 cycles is as high as 253.6mAh / g, and the charge and discharge efficiency is as high as 98.3%.

[0070] Fig.17 Given Sb 0.4 Bi 0.4 Sn 0.3 Co 0.3 Ni 0.3 Mn 0.3 The rate performance diagram of Te3 negative electrode material in the potassium storage process shows that the reversible specific capacity at current densities of 50, 100, 200, 500, 1000, and 2000 mA / g is 215.0, 172.4, 148.5, 116.1, 71.9, and 36.8 mAh / g, respectively. When the current is restored to 50 mA / g, the reversible specific capacity can be restored to 195.4 mAh / g.

[0071] It can be seen that pure phase Sb was successfully prepared by hydrothermal method. 0.4 Bi 0.4 Sn 0.3 Co 0.3 Ni 0.3 Mn 0.3 Te3-based hexavalent high-entropy anode material. High entropy and cocktail effect significantly improve the electrochemical kinetic behavior and electrode stability, so the electrode material exhibits high reversible specific capacity, excellent cycle stability and rate performance.

[0072] Example 4

[0073] (1) 0.5 mmol antimony trichloride, 0.1 mmol bismuth trichloride, 0.1 mmol stannous chloride, 0.1 mmol cobalt sulfate, 0.1 mmol nickel sulfate, and 0.1 mmol manganese sulfate were dissolved in 10 ml deionized water containing 1.0 g tartaric acid to form a uniform solution A; secondly, 1.3 mmol sodium tellurite was dissolved in 40 ml ammonia water containing 16 ml hydrazine hydrate to form a uniform solution B;

[0074] (2) Solution A and Solution B were stirred at 30°C for 3 h, transferred to a reaction vessel lined with polytetrafluoroethylene, and kept at 150°C for 10 h for hydrothermal reaction;

[0075] (3) After cooling to room temperature, the precipitate was obtained by centrifugation, and the precipitate was washed with deionized water and ethanol, and finally vacuum dried at 100°C for 6 h to obtain the target product Sb 1.0 Bi 0.2 Sn 0.2 Co 0.2 Ni 0.2 Mn 0.2 Te3.

[0076] Example 5

[0077] (1) 0.4 mmol antimony trichloride, 0.2 mmol bismuth trichloride, 0.1 mmol stannous chloride, 0.1 mmol cobalt chloride, 0.1 mmol nickel chloride, and 0.1 mmol manganese chloride were dissolved in 10 ml deionized water containing 1.0 g tartaric acid to form a uniform solution A; secondly, 1.55 mmol sodium tellurite was dissolved in 40 ml ammonia water containing 16 ml hydrazine hydrate to form a uniform solution B;

[0078] (2) stirring solution A and solution B at 40° C. for 2 h, transferring them to a reaction vessel lined with polytetrafluoroethylene, and keeping them at 120° C. for 12 h for hydrothermal reaction;

[0079] (3) After cooling to room temperature, the precipitate was obtained by centrifugation, and the precipitate was washed with deionized water and ethanol, and finally vacuum dried at 50°C for 36 hours to obtain the target product Sb 0.8 Bi 0.4 Sn 0.2 Co 0.2 Ni 0.2 Mn 0.2 Te3.

[0080] Example 6

[0081] (1) 0.3 mmol antimony nitrate, 0.2 mmol bismuth nitrate, 0.2 mmol stannous chloride, 0.1 mmol cobalt chloride, 0.1 mmol nickel chloride, and 0.1 mmol manganese chloride were dissolved in 10 ml deionized water containing 1.0 g tartaric acid to form a uniform solution A; secondly, 1.5 mmol sodium tellurite was dissolved in 40 ml ammonia water containing 16 ml hydrazine hydrate to form a uniform solution B;

[0082] (2) stirring solution A and solution B at 50° C. for 1.5 h, transferring them to a reactor lined with polytetrafluoroethylene, and keeping them at 140° C. for 10 h for hydrothermal reaction;

[0083] (3) After cooling to room temperature, the precipitate was obtained by centrifugation, and the precipitate was washed with deionized water and ethanol, and finally vacuum dried at 60°C for 24 h to obtain the target product Sb 0.6 Bi 0.4 Sn 0.4 Co 0.2 Ni 0.2 Mn 0.2 Te3.

[0084] Example 7

[0085] (1) 0.25 mmol antimony nitrate, 0.25 mmol bismuth nitrate, 0.25 mmol stannous chloride, 0.15 mmol nickel chloride, and 0.1 mmol manganese chloride were dissolved in 10 ml deionized water containing 1.0 g tartaric acid to form a uniform solution A; secondly, 1.45 mmol sodium tellurite was dissolved in 40 ml ammonia water containing 16 ml hydrazine hydrate to form a uniform solution B;

[0086] (2) Solution A and Solution B were stirred at 60°C for 1 h, transferred to a reaction vessel lined with polytetrafluoroethylene, and kept at 150°C for 8 h for hydrothermal reaction;

[0087] (3) After cooling to room temperature, the precipitate was obtained by centrifugation, and the precipitate was washed with deionized water and ethanol, and finally vacuum dried at 80°C for 16 h to obtain the target product Sb 0.5 Bi 0.5 Sn 0.5 Ni 0.3 Mn 0.2 Te3.

[0088] Example 8

[0089] (1) 0.2 mmol antimony nitrate, 0.2 mmol bismuth nitrate, 0.2 mmol stannous chloride, 0.2 mmol cobalt nitrate, and 0.2 mmol nickel sulfate were dissolved in 10 ml deionized water containing 1.0 g tartaric acid to form a uniform solution A; secondly, 1.4 mmol sodium tellurite was dissolved in 40 ml ammonia water containing 16 ml hydrazine hydrate to form a uniform solution B;

[0090] (2) Solution A and Solution B were stirred at 60°C for 1 h, transferred to a reaction vessel lined with polytetrafluoroethylene, and kept at 180°C for 6 h for hydrothermal reaction;

[0091] (3) After cooling to room temperature, the precipitate was obtained by centrifugation, and the precipitate was washed with deionized water and ethanol, and finally vacuum dried at 70°C for 20 h to obtain the target product Sb 0.4 Bi 0.4 Sn 0.4 Co 0.4 Ni 0.4 Te3.

[0092] It should be noted that the above-described embodiments are only preferred embodiments of the present invention. For those skilled in the art, without departing from the principles of the present invention, the present invention may be modified, improved and replaced with equivalents, and these modifications, improvements and equivalent replacements are also considered to fall within the scope of protection of the claims of the present invention.

Claims

1. A high entropy conversion-alloy-based negative electrode material in a potassium / sodium ion battery, characterized in that: The chemical formula of the negative electrode material is Sb x Bi y Sn z Co m Mn n Ni 2-x-y-z-m-n Te3, wherein 0≤x<2, 0≤y<2, 0≤z<2, 0≤m<2, 0≤n<2, and at least three elements among Sb, Bi, Sn, Co, Mn, and Ni are present.

2. A method for preparing a high entropy conversion-alloy-based negative electrode material in a potassium / sodium ion battery according to claim 1, characterized in that: The following steps are involved: (1) weighing a certain amount of antimony salt, bismuth salt, tin salt, cobalt salt, manganese salt and nickel salt according to a stoichiometric ratio and dissolving them in deionized water containing tartaric acid to form a uniform solution A; secondly dissolving a certain amount of sodium tellurite in ammonia water containing hydrazine hydrate to form a uniform solution B; (2) mixing the solution A and the solution B evenly under stirring conditions, transferring the mixture to a reaction kettle lined with polytetrafluoroethylene, and performing a hydrothermal reaction under certain temperature and time conditions; (3) obtaining a precipitate by centrifugation or filtration, washing the precipitate with deionized water and ethanol, and finally obtaining the target product Sb by vacuum drying. x Bi y Sn z Co m Mn n Ni 2-x-y-z-m-n Te3.

3. The method for preparing a high entropy conversion-alloy-based negative electrode material in a potassium / sodium ion battery according to claim 2, characterized in that: The antimony salt, bismuth salt, tin salt, cobalt salt, manganese salt and nickel salt described in step (1) can be one or more of chloride, sulfate and nitrate.

4. The method for preparing a high entropy conversion-alloy-based negative electrode material in a potassium / sodium ion battery according to claim 2, characterized in that: The molar ratio of the sodium tellurite to the total amount of the metal salt in step (1) is 2.5 to 3.1:

2.

5. The method for preparing a high entropy conversion-alloy-based negative electrode material in a potassium / sodium ion battery according to claim 2, characterized in that: In step (2), the stirring temperature is 20 to 60° C. and the stirring time is 0.5 to 4 h.

6. The method for preparing a high entropy conversion-alloy-based negative electrode material in a potassium / sodium ion battery according to claim 2, characterized in that: The hydrothermal reaction temperature in step (2) is 120-220° C., and the hydrothermal reaction insulation time is 2-12 hours.

7. The method for preparing a high entropy conversion-alloy-based negative electrode material in a potassium / sodium ion battery according to claim 2, characterized in that: The vacuum drying temperature in step (3) is 50-100° C., and the vacuum drying time is 6-36 hours.

Citation Information

Patent Citations

  • Bismuth antimony telluride / graphene potassium ion battery negative electrode material with high-stability structure and preparation method thereof

    CN113130908A

  • Preparation method and application of high-entropy negative electrode material

    CN118073559A

  • High-entropy sodium alloy negative electrode, preparation method and sodium battery

    CN118448585A

  • Negative electrode active material for secondary battery, and secondary battery

    WO2023053887A1